A Framework for Discipline-Specific Learning, Teaching, and Assessment of Psychomotor Skills in Higher Education - Matshete Chweu, Eric (International Journal on Higher Education Issues, 2025)
This study investigated the extent to which psychomotor skills are assessed in higher education and proposed a framework to enhance the assessment of these skills. While higher education institutions globally assess students' knowledge thoroughly, the assessment of psychomotor skills is often implicit, unsystematic, and inadequate. This research aims to address this gap by using Bloom's taxonomy to develop a comprehensive assessment framework. The research question was: "How can Bloom's taxonomy’s psychomotor domain be used to create a framework for assessing psychomotor skills?" A quantitative method was employed, utilizing the Trilogy Assessment Psychomotor Domain Inventory to gather data from 268 South African University of Technology lecturers. Analysis with SPSS version 28.0 and reliability testing showed high internal consistency. Findings revealed that 54% of lecturers did not assess psychomotor skills, highlighting the necessity for a structured assessment framework to improve learning and teaching outcomes.